The Islamic republic of Iran’s networking diplomacy: the role of Ahl-ul-Bayt World Assembly (ABWA) - Ra'ees, Wahabuddin; Bani Kamal, Abdol Moghst (IIUM Press, International Islamic University Malaysia, 2017)
The 1979 Iranian Revolution entailed establishing Iran’s hegemony in the region and promotion of shi’ite doctrinal values in the Muslim world. The Iranian State under the leadersip of Ayatullah Khomeini was tasked to design a strategy of organizing and connecting the non-Iranian Shi’ites and Sunnite sympathisers of the revolution particulary in the Muslim world with the Islamic Republic of Iran. Networking with the non-Iranian Shi’ites and Sunnite sympathizers of the revolution was crucial for support for Iran’s hegemony and export of the revolution. The Islamic Republic established Ahl-ul-bayt World Assembly (ABWA) to carry out its networking diplomacy. ABWA’s objectives, networking strategies and activities in Afghanistan and Malaysia suggest that the non-Iranian Shi’ites and Sunnite sympathizers of the Revoltion are political and strategic asset and Iran under the guise of the narrative of exporting revoltion expects their loyalty and sympathy rather than to the state of their citizenship and residence. Unlike Malaysia, ABWA’s networking activity in Afghanistan also entails integrating the Afghan Shi’ites into sensitive positions in the post-Taliban political system, indeed a breach of the claim that ABWA is apolitical and neutral institution.